2014
DOI: 10.3389/fphys.2014.00072
|View full text |Cite
|
Sign up to set email alerts
|

Roles of dopamine receptor on chemosensory and mechanosensory primary cilia in renal epithelial cells

Abstract: Dopamine plays a number of important physiological roles. However, activation of dopamine receptor type-5 (DR5) and its effect in renal epithelial cells have not been studied. Here, we show for the first time that DR5 is localized to primary cilia of LLCPK kidney cells. Renal epithelial cilia are mechanosensory organelles that sense and respond to tubular fluid-flow in the kidney. To determine the roles of DR5 and sensory cilia, we used dopamine to non-selectively and fenoldopam to selectively activate ciliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Fenoldopam mesylate (Sigma) was used at 10 μM diluted in DMSO, dimethyl sulfoxide, (Sigma) and normal culture media, as previously described (Kathem et al, 2014; Upadhyay et al, 2014). Lithium chloride (Sigma) was used at 500 μM diluted in normal culture media – a dose response from 50 μM to 10 mM was examined with 500 μM being the lowest dose to increase length significantly, data not shown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenoldopam mesylate (Sigma) was used at 10 μM diluted in DMSO, dimethyl sulfoxide, (Sigma) and normal culture media, as previously described (Kathem et al, 2014; Upadhyay et al, 2014). Lithium chloride (Sigma) was used at 500 μM diluted in normal culture media – a dose response from 50 μM to 10 mM was examined with 500 μM being the lowest dose to increase length significantly, data not shown.…”
Section: Methodsmentioning
confidence: 99%
“…Fenoldopam is a dopamine D1-like receptor agonist, and has previously been used to increase primary cilia length in endothelial cells and kidney epithelial cells, potentially through an adenylyl cyclase-cAMP mechanism (Kathem et al, 2014; Upadhyay et al, 2014). In the context of bone, MC3T3 osteoblasts express dopamine receptors 1-5, yet the role of specific dopamine receptors and the effects of fenoldopam treatment is unknown, and has never been examined in MLOY4 osteocytes (Lee et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dopamine inhibits flow-stimulated NHE3 activity by activation of the D1R receptor via a PKA-mediated mechanism, modulating proximal tubule transporters [27]. A potentially novel mechanism of activation of dopamine receptors in response to luminal flow was recently reported by Upadhyay et al [28 ▪ ]. They localized D5R to primary cilia in pig kidney epithelial cells.…”
Section: New Insights Into Renal Dopamine Signalling and Functionmentioning
confidence: 99%
“…Activation of D5R with either dopamine or fenoldopam increased primary cilia length in association with an increased sensitivity of the cells in response to fluid-shear stress. This finding suggests a potential role for intrarenal dopamine signal transduction in response to volume expansion and also raises the possibility that dopaminergic agonists might be used as potential agents to treat diseases associated with abnormal cilia structure and/or function [28 ▪ ]. …”
Section: New Insights Into Renal Dopamine Signalling and Functionmentioning
confidence: 99%
“…Both laboratories showed that bending primary cilia with a micropipette or with fluid flow activates the cilium and increases cytoplasmic calcium in renal epithelial cells. Since then, other laboratories have utilized intracellular calcium as a read-out to understand the functions of primary cilia in vascular endothelial cells (32, 33), renal epithelial cells (34-36), eye trabecular meshwork cells (37), nodal cells (19, 21), hepatocytes (17, 22), osteocytes (38), and chondrocytes (39). …”
Section: Primary Cilia and Intracellular Read-outmentioning
confidence: 99%